The Public Administration Paradigm in Managing Search and Rescue (SAR) Operations at the Gorontalo Search and Rescue Office - Malasari M; Rusli Isa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This article discusses the application of the public administration paradigm in the management of Search and Rescue (SAR) operations at the Gorontalo Search and Rescue Office. Using a descriptive qualitative approach, this study highlights how modern public administration principles—such as effectiveness, efficiency, accountability, and cross-sector collaboration—are applied within the operational context of SAR. The findings indicate that the Gorontalo Search and Rescue Office has adopted several principles of New Public Management (NPM) and Good Governance, but still faces challenges in inter-agency coordination, limited human resources and equipment, as well as a lack of public information transparency. The article concludes with strategic recommendations to strengthen governance and improve the performance of SAR operations in Gorontalo.